Online Teaching Practicum in Malaysia in the Time of COVID-19 Pandemic - Annamalai, Nagaletchimee; Ab Rashid, Radzuwan; Harb Alqaryouti, Marwan; Eddin Sadeq, Ala; Al-Smadi, Omar Ali; Kumar, Jeya Amantha (Frontiers in Psychology, 2022)
When the teachers’ training practicum was paralyzed during the COVID-19 pandemic, preservice teachers in Malaysia were required to adapt to the online practicum. This qualitative case study was conducted with 20 preservice teachers to investigate their online teaching practicum experiences. The study drew on the Engagement Theory and Disaster Management Cycle framework to further suggest teaching approaches that might be effective during a tragic situation. Data were collected from interviews and video observations, and analyzed thematically. The findings contribute to the understanding of how preservice teachers learn to modify their teaching practices during the challenging context. A number of themes related to positive experience were identified: (i) higher confidence level, (ii) improved interaction, (iii) engagement in active learning, and (iv) adapting to online syllabus. On the other hand, the negative experience revolves around the problem with Internet connection. It is hoped that the findings of this study will encourage preservice teachers to consider hybrid approaches and online teaching in the future.